Preservation of residual hearing after cochlear implant surgery: an exploration of residual hearing function in a group of recipients at cochlear implant units - Katherine Gautschi-Mills; Katijah Khoza-Shangase; Dhanashree Pillay (Brazilian Journal of Otorhinolaryngology, 2019)
Introduction: The preservation of residual hearing is becoming increasingly important in cochlear implant surgery. Conserving residual hearing is a positive prognostic indicator for improved hearing abilities. Objective: The primary aim of the study was to explore the preservation of residual hearing following cochlear implantation in a group of recipients at two major cochlear implant centers. Methods: A quantitative paradigm was adopted and exploratory research conducted within a retrospective data review design. The sample consisted of 50 surgical records and 53 audiological records from 60 observations (53 patients, seven of whom were implanted bilaterally). The records were selected using purposive sampling and consisted of records from participants ranging from six to 59 years of age. The average time of when the postoperative audiograms were performed in the current study was 24.7 months (s.d. = ±9.0). Data were analyzed through both qualitative and inferential statistics and a comparative analysis of unaided pre- and postoperative audiological test results was conducted. Results: Results indicated a high success rate of 92% preservation of residual hearing with half of the sample exhibiting complete preservation in cochlear implant recipients across all frequencies postoperatively. A total postoperative hearing loss was found in only 8% of cochlear implantees across all frequencies. There was no relationship between preoperative hearing thresholds and preservation of hearing postoperatively. The two main surgical techniques used in the current study were the contour on stylet and the advance off-stylet techniques, with the majority of surgeons utilizing a cochleostomy approach. From the findings, it became apparent that the majority of cases did not have any reported intraoperative complications. This is a positive prognostic indicator for the preservation of residual hearing. Conclusion: Findings suggest improved cochlear implant surgical outcomes when compared to previous studies implying progress in surgical techniques. The surgical skill and experience of the surgeon are evidenced by the minimal intraoperative complications and the high success rate of hearing preservation. This is a positive prognostic indicator for individuals with preoperative residual hearing as the preserved residual hearing allows for the potential of electro-acoustic stimulation, which in turn has its own hearing benefits. Resumo: Introdução: A preservação da audição residual tem se tornado cada vez mais importante na cirurgia de implante coclear. Conservar a audição residual é um indicador prognóstico positivo para melhorar as habilidades auditivas. Objetivo: Avaliar a preservação da audição residual pós-implante coclear em um grupo de pacientes de dois grandes centros de implantes cocleares. Método: Foram adotados um paradigma quantitativo e uma pesquisa exploratória em um projeto retrospectivo de revisão de dados. A amostra consistiu de 50 registros cirúrgicos e 53 registros audiológicos de 60 observações (53 pacientes, sete dos quais foram implantados bilateralmente). Os registros foram selecionados com amostragem proposital e consistiram em registros de participantes de seis a 59 anos. Neste estudo, o tempo médio para audiogramas no pós-operatório foi de 24,7 meses (dp = ± 9,0). Os dados foram analisados através de estatísticas qualitativas e inferenciais, foi feita uma análise comparativa de resultados de testes audiológicos pré e pós-operatórios, sem auxílio de aparelho auditivo. Resultados: Os resultados indicaram uma alta taxa de sucesso, de 92%, de preservação da audição residual, metade da amostra dos implantados exibia preservação completa em todas as frequências no pós-operatório. Perda auditiva total em todas as frequências no pós-operatório foi observada em apenas 8% dos implantes cocleares. Não houve relação entre limiares auditivos pré-operatórios e preservação auditiva no pós-operatório. As duas principais técnicas cirúrgicas usadas no presente estudo foram contour on stylet e a técnica advance off-stylet e a maioria dos cirurgiões usou uma abordagem por cocleostomia. A partir dos achados, tornou-se evidente que a maioria dos casos não apresentou complicação intraoperatória. Esse é um indicador prognóstico positivo para a preservação da audição residual. Conclusão: Os achados sugerem melhoria dos resultados cirúrgicos do implante coclear quando comparados com estudos prévios, sugerem um progresso nas técnicas cirúrgicas. A habilidade cirúrgica e a experiência do cirurgião são evidenciadas pelas complicações intraoperatórias mínimas e pela alta taxa de sucesso de preservação auditiva. Esse é um indicador prognóstico positivo para indivíduos com audição residual pré-operatória, uma vez que a audição residual preservada possibilita o potencial de estimulação eletroacústica (EAS – do inglês Electric Acoustic Stimulation), que, por sua vez, tem benefícios auditivos próprios. Keywords: Audiological, Cochlear implant, Preservation, Hearing, Surgical technique, Palavras-chave: Audiológico, Implante coclear, Preservação, Audição, Técnica cirúrgica